A Novel Diagnostic and Prognostic Score for Abdominal Aortic Aneurysms Based on D-Dimer and a Comprehensive Analysis of Myeloid Cell Parameters - Zagrapan, Branislav; Eilenberg, Wolf; Prausmueller, Suriya; Nawrozi, Paimann; Muench, Katharina; Hetzer, Sarah; Elleder, Vanessa; Rajic, Renata; Juster, Felix; Martelanz, Luca; Hayden, Hubert; Klopf, Johannes; Inan, Cansu; Teubenbacher, Peter; Weigl, Markus P.; Kirchweger, Patrick; Beitzke, Dietrich; Jilma, Bernd; Wojta, Johann; Bailey, Marc A.; Scott, D. Julian A.; Huk, Ihor; Neumayer, Christoph; Brostjan, Christine (Thrombosis and Haemostasis, 2019)
The pathogenesis of abdominal aortic aneurysm (AAA) involves a central component of chronic inflammation which is predominantly mediated by myeloid cells. We hypothesized that the local inflammatory activity may be reflected in systemic alterations of neutrophil and monocyte populations as well as in soluble factors of myeloid cell activation and recruitment. To establish their marker potential, neutrophil and monocyte sub-sets were measured by flow cytometry in peripheral blood samples of 41 AAA patients and 38 healthy controls matched for age, sex, body mass index and smoking habit. Comparably, circulating factors reflecting neutrophil and monocyte activation and recruitment were assayed in plasma. Significantly elevated levels of CD16+ monocytes, activated neutrophils and newly released neutrophils were recorded for AAA patients compared with controls. In line, the monocyte chemoattractant C-C chemokine ligand 2 and myeloperoxidase were significantly increased in patients' plasma. The diagnostic value was highest for myeloperoxidase, a mediator which is released by activated neutrophils as well as CD16+ monocytes. Multivariable regression models using myeloid activation markers and routine laboratory parameters identified myeloperoxidase and D-dimer as strong independent correlates of AAA. These two biomarkers were combined to yield a diagnostic score which was subsequently challenged for confounders and confirmed in a validation cohort matched for cardiovascular disease. Importantly, the score was also found suited to predict rapid disease progression. In conclusion, D-dimer and myeloperoxidase represent two sensitive biomarkers of AAA which reflect distinct hallmarks (thrombus formation and inflammation) of the pathomechanism and, when combined, may serve as diagnostic and prognostic AAA score warranting further evaluation.
Keywords: abdominal aortic aneurysm; D-dimer; diagnosis; myeloperoxidase; prognosis